(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2018)
Background: Tuberculosis (TB) is one of the commonest infectious diseases in the developing countries like Bangladesh. Tubercular Meningitis (TBM) is a common sequel of TB involving the Central Nervous System (CNS) and is one of the leading causes of mortality and morbidity. Syringomyelia following TBM as late or early complication of TB is very rare. Case Description: We report a case of syrigomyelia in a 32 years old lady as a sequel, following treatment for tubercular meningitis after 8 years of successful treatment of tubercular meningitis with a full course of Anti tubercular drugs. She developed gradual weakness of her both lower limbs along with tingling and numbness and bladder incontinence for 5 months before presentation. MRI of Brain and Spine revealed syringomyelia from upper cervical region down to lower dorsal region. Syringostomy at D7 level was done initially but with not much significant improvement. Rather over a period of time she deteriorated and became bed ridden. We put a syringoperitoneal shunt. One month after surgery her lower limb power improved to MRC Grade 4 which enabled her to walk with support. She also had significant improvement of bladder function with full control. Conclusion: High index of suspicion with new neurological signs in patients of TBM, despite proper treatment, is worthwhile considering syringomyelia as a possible cause. Timely diagnosis and appropriate treatment thereby can reduce the morbidity with better neurological outcome. JCMCTA 2017 ; 28 (2) : 116-121